Static and dynamic quantity-setting games: An in-class experiment - Raguseo, DomeNico (Business: Theory and Practice, 2009)
This paper illustrates the results of a case study on teaching economics issues employing an experiment where students were made to play quantity-setting games employing the Stackelberg and Cournot theory of oligopoly. A strictly theoretical approach to the study of the oligopolistic market structure is replaced by a discovery-learning method. The goal of the in-class experiment is both to illustrate to students the economics theory through learning by doing approach and to allow the instructors to discover how students act when they have to develop their own strategies, placing them in a role similar to that of firms aiming to maximize the profits. The main finding shows how students converged toward the Nash-equilibrium quantity. Several firms or groups of students, who were producing high output level at the beginning of the game later on reduced their output since they realized that their profit could increase by just producing less. At the end of the experiment, students have emphasized that they have really learned what it is like to interact in a market structure where firms can influence the market variables but not absolutely control them.Žaidybinio mokymo metodo taikymas mokymo proceseSantrauka. Straipsnyje aprašomi žaidybinio mokymo metodo taikymo studentų mokymo procese rezultatai. Dalykinio žaidimo metu studentai taikė Stackelberg ir Cournot oligopolinę teoriją. Vietoj griežtai teorinio mokymo metodo apie oligopolinės rinkos struktūrą buvo taikomas aktyvus mokymosi metodas. Rezultatai parodė, kad tai originalus, įdomus ir naudingas būdas, padedantis geriau suprasti oligopolinės rinkos struktūrą, siejantis teoriją su praktiniais pavyzdžiais.Reikšminiai žodžiai: eksperimentinė ekonomika, oligopolija, lošimų teorija.First Published Online: 10 Dec 2009